2018
DOI: 10.1002/mrd.22975
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preimplantational oral low‐dose estradiol‐17β exposure on the endometrium: The role of miRNA

Abstract: Porcine conceptuses synthesize estrogens between Day 11 and 12 as signal for maternal recognition of pregnancy. A preimplantational estrogen exposure to pregnant gilts has been associated with embryonic losses and changes in endometrial mRNA expression. MicroRNAs (miRNAs) play a key role in the mRNA regulation by modulating the expression. Effects of estrogens on endometrial miRNAs have not been investigated in this context so far. Thus, we studied the endometrial expression profile of miRNAs in the pig at ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…Our studies suggested a similar regulatory relationship in the porcine endometrium [23]. However, neither endometrium [47] nor blastocyst [38] miRNAome was shown to be affected on day 10 of pregnancy by E2 administered daily to sows in different doses, even though its concentrations significantly increased in the endometrium.…”
Section: Mirnas At the Embryo-maternal Interfacesupporting
confidence: 55%
“…Our studies suggested a similar regulatory relationship in the porcine endometrium [23]. However, neither endometrium [47] nor blastocyst [38] miRNAome was shown to be affected on day 10 of pregnancy by E2 administered daily to sows in different doses, even though its concentrations significantly increased in the endometrium.…”
Section: Mirnas At the Embryo-maternal Interfacesupporting
confidence: 55%
“…The increasing concentrations of E2 and/or its metabolites reaching the uterus as depicted in this manuscript and elsewhere [64], respectively, are one possible explanation for the expression differences found in the NOEL and the high dose group compared to the control animals. Despite a 160-fold increase in unconjugated total estrogens in the endometrium, there was no difference in the number of offspring at birth after treatment over the entire pregnancy [10].…”
Section: Discussionsupporting
confidence: 50%
“…In addition, the continuous E2 exposure did not lead to embryonic losses [10]. Interestingly, our preimplantation E2 exposure did not affect the endometrial miRNA expression profile [64].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A previous study has shown that highly expressed miRNAs may play vital roles in the regulation of embryo implantation [30]. The expression of top 20 most highly expressed known miRNAs in ULF exosomes was compared with that in endometrium [31] and embryo [29] collected on D10. Among these miRNAs, ssc-miR-21-5p was the most abundant in all libraries.…”
Section: Discussionmentioning
confidence: 99%